(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Urinary incontinence and pelvic floor dysfunctions are highly prevalent and often under-reported conditions that negatively affect quality of life, general health, and social participation. To inform the development of a new eHealth intervention, we first conducted a rapid review of mobile technologies and websites for self-management of bladder health and urinary incontinence in adults aged 50+. Only four evidence-based digital solutions were identified, none of which had been co-designed with older adults or integrated comprehensive behaviour-change strategies, social support, and structured gamification. KOKU Bladder (“Keep On Keep Up your Bladder health”) was subsequently co-designed through eight expert interviews and six multi-stakeholder focus groups conducted in Spain, Lithuania, and the United Kingdom, involving 29 end-users, 13 healthcare professionals, and two key stakeholders. Participants highlighted the need for a discreet, credible, and inclusive digital solution offering progressive pelvic floor muscle training with clear audiovisual guidance, practical bladder and lifestyle education, robust behaviour-change support (e.g. reminders, feedback, and goal-setting), engaging gamification, meaningful personalisation, and moderated professional and peer support within a secure community to reduce stigma and sustain long-term adherence. The resulting first version of the eHealth programme integrates five components: 20 educational videos complemented by external resources; 21 progressive pelvic floor exercise programmes across five levels; a professional–user chat; a moderated virtual support community; and an educational game. The platform is currently being evaluated through multilingual usability testing in Spanish, Lithuanian, and English. A feasibility and acceptability pilot study will follow, recruiting at least 120 participants across the three countries to further examine feasibility, acceptability, and preliminary effects on health outcomes. Keywords: eHealth; urinary incontinence; bladder health; co-design; ageing